The Use of Pelmanism Game to Increase Vocabulary at SDIT Ya Bunayya Pujon- Malang - Ika Jati Rahayu (Verba: Journal of Applied Linguistics, 2022)
The problem in this research is "How can Pelmanism Game increase vocabulary for the fourth grade students at SDIT Ya Bunayya Pujon - Malang?" The objective of this research is “To increase vocabulary by using Pelmanism Games for the fourth grade students at SDIT Ya Bunayya Pujon – Malang”. The method used in this research was CAR (Classroom Action Research) which consists of four phases, namely planning, acting, observing, and reflecting. The subjects of this study were the fourth grade students of SDIT Ya Bunayya Pujon, academic year 2019/2020, which consist of 35 students. This research was carryout in two cycles. The instruments used in data collection were observation and written tests. The researcher used the KKM score of 75 for students who meet the criteria, and 75% of all students get the KKM value / above KKM as a measure of success. Based on the preliminary test, there were only 6 students who meet the criteria (17.14%). In Cycle 1 there was an increase, 23 students who meet the criteria (65.71%). And a significant increase occurred in cycle 2, there were 30 students who meet the criteria (85.71%). The research finding show that there was an increase in the scores obtained by students from the preliminary test to the post-test cycle 2. So the researchers conclude that the use of Pelmanism Games can improve the vocabulary mastery of students at SDIT Ya Bunayya Pujon Malang.